(untitled) (Research, Society and Development, 2022)
Objective: To associate clinical data between the Pediatric Dysphagia Risk Screening Instrument – IRRD-Ped and the findings of the clinical evaluation of swallowing through the Pediatric Dysphagia Clinical Assessment Protocol – PAD-PED in wheezing infants, without other comorbidities. Methodology: This is an observational, cross-sectional, controlled and accurate clinical research study. Two groups were formalized: Group A, cases, formed by 10 wheezing infants; and Group B, control, formed by 13 infants without known risk factors for dysphagia. The IRRD-PED was applied and clinical assessments were performed using the PAD-PED and, when necessary, an objective assessment of swallowing was carried out using Videofluoroscopy of Swallowing – VFS. Results: The final IRRD-Ped score identified a higher risk for oropharyngeal dysphagia in Group A (p-value of 0.001). All members of Group A presented some degree of dysphagia in the clinical evaluation performed with the PAD-PED, showing a strong association with the result found in the application of the IRRD-Ped. The IRRD-Ped items most relevant to the identification of risk for dysphagia were: occurrence of frequent colds, previous pneumonia and changes in breathing pattern after eating. Nine infants were assessed by VFS and identified with dysphagia Conclusion: There was a strong association between the data collected between the screening instrument and the clinical evaluation protocol in children with respiratory compromise. The use of the IRRD-PED proved to be efficient for the detection of risk for pediatric dysphagia in the studied sample.